Traumatic Brain Injury Diminishes Feedforward Activation of Parvalbumin-Expressing Interneurons in the Dentate Gyrus - Folweiler, Kaitlin A. (eNeuro, 2020)
Traumatic brain injury (TBI) is associated with aberrant network hyperexcitability in the dentate gyrus (DG). GABA(A)ergic parvalbumin-expressing interneurons (PV-INs) in the DG regulate network excitability with strong, perisomatic inhibition, although the posttraumatic effects on PV-IN function after TBI are not well understood. In this study, we investigated physiological alterations in PV-INs one week after mild lateral fluid percussion injury (LFPI) in mice. PV-IN cell loss was observed in the dentate hilus after LFPI, with surviving PV-INs showing no change in intrinsic membrane properties. Whole-cell voltage clamp recordings in PV-INs revealed alterations in both EPSCs and IPSCs (EPSCs/IPSCs). Evoked EPSCs (eEPSCs) in PV-INs from perforant path electrical stimulation were diminished after injury but could be recovered with application of a GABA(A)-receptor antagonist. Furthermore, current-clamp recordings using minimal perforant path stimulation demonstrated a decrease in evoked PV-IN action potentials (APs) after LFPI, which could be restored by blocking GABA(A)ergic inhibition. Together, these findings suggest that injury alters synaptic input onto PV-INs, resulting in a net inhibitory effect that reduces feedforward PV-IN activation in the DG. Decreased PV-IN activation suggests a potential mechanism of DG network hyperexcitability contributing to hippocampal dysfunction after TBI.